Control of Leishmania major by a monoclonal alpha beta T cell repertoire - Reiner, S L; Fowell, D J; Moskowitz, N H; Swier, K; Brown, D R; Brown, C R; Turck, C W; Scott, P A; Killeen, N; Locksley, R M (The Journal of immunology (1950), 1998)
Little is known regarding the diversity of the host T cell response that is required to maintain immunologic control of microbial pathogens. Leishmania major persist as obligate intracellular parasites within macrophages of the mammalian host. Immunity is dependent upon activation of MHC class II-restricted T cells to an effector state capable of restricting growth and dissemination of the organisms. We generated alpha-beta Leishmania-specific (ABLE) TCR transgenic mice with MHC class II-restricted T cells that recognized an immunodominant Leishmania Ag designated LACK. Naive T cells from ABLE mice proliferated in vitro after incubation with recombinant LACK or with Leishmania-parasitized macrophages and in vivo after injection into infected mice. Infected ABLE mice controlled Leishmania infection almost as well as wild-type mice despite a drastic reduction in the T cell repertoire. ABLE mice were crossed to mice with disruption of the TCR constant region alpha gene to create animals with a single alpha beta T cell repertoire. Although mice deficient in all alpha beta T cells (TCR-C alpha 0 mice) failed to control L. major, mice with a monoclonal alpha beta T cell repertoire (ABLE TCR-C alpha 0 mice) displayed substantial control. The immune system is capable of remarkable efficiency even when constrained to recognition of a single epitope from a complex organism.